2019
DOI: 10.1177/1533033819870815
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic Ablative Radiotherapy for Prostate Cancer—The Treatment Results of 500 Patients and Analysis of Failures

Abstract: Objective: Stereotactic ablative radiotherapy is a very promising approach for the treatment of patients with prostate cancer. The aim of this study was to evaluate the clinical tolerance, effectiveness, patterns of failure, and attempt to define predictive factors based on our experience. Methods: The cohort consists of 264 low-risk and 236 intermediate-risk consecutive patients treated at one institution. Prostate-specific antigen (PSA), adverse effects, and androgen deprivation therapy (ADT) usage were note… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…UHRT is generally well tolerated, and in a previous publication regarding side effects, we have observed that over 90% and 75% of patients report no gastro-intestinal and genito–urinary toxicity, respectively [ 18 ]. LDR-BT and HDR-BT have also been shown to present favourable toxicity profiles [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…UHRT is generally well tolerated, and in a previous publication regarding side effects, we have observed that over 90% and 75% of patients report no gastro-intestinal and genito–urinary toxicity, respectively [ 18 ]. LDR-BT and HDR-BT have also been shown to present favourable toxicity profiles [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to conventionally fractionated RT, UHRT also takes advantage of the low α/β ratio of PCa, which signalizes a high sensitivity to increases in fraction doses [ 12 , 13 , 14 , 15 ]. Prospective randomized clinical trials have shown non-inferiority of UHRT [ 16 , 17 ], which is supported by the real-world data showing an excellent toxicity profile, and as few as 3% clinical failures at a median FU of 31.3 months [ 18 ]. Moreover, as metastases-directed therapy and local salvage methods for local–regional recurrences have been considered a standard of care at our institution for over a decade, we recorded a significant subset of clinical failures treated with ‘second-line definitive treatment’.…”
Section: Introductionmentioning
confidence: 91%
“…We performed a retrospective analysis of an institutional registry of 500 consecutive patients treated with ultra-hypofractionated stereotactic CyberKnife RT for localized N0 NCCN low- or intermediate risk-group PCa between 2011 and 2017 [ 12 ]. After the exclusion of 271 patients due to initiation of androgen deprivation therapy (ADT) before MRI, and 77 patients due to missing MRI series, the final analysis included 152 patients.…”
Section: Methodsmentioning
confidence: 99%
“…In radiation therapy, PI-RADS could help to improve pre-treatment patient selection for tailored definitive therapy. Thus, we aimed to analyze the prognostic value of pre-treatment prostate MRI PI-RADS v2.1 based on a cohort of patients treated with ultra-hypofractionated CyberKnife radiotherapy for early-stage PCa [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…SABR helps with postponing the progression and continuation of chemotherapy and also increases the quality of life (27). By using SABR technique, primary irradiation of low risk and intermediate risk prostate carcinomas has proven to be a successful, effective and safe method, as only 3% of treatment (among 500 patients) was unsuccessful (28). Studies have shown that patients with early stage, non-small cell lung cancer can be treated with SABR as an alternative to a radical surgical procedure.…”
Section: Stereotactic Body Radiotherapy (Sbrt)mentioning
confidence: 99%